Особливості соціально- правових уявлень військовослужбовців - Худавердова, А. О.; Khudaverdova, A. O. (Вісник Львівського університету. Сер.: Психологічні науки. - 2022. - Вип.14. - С. 76-82, 2022)
Відзначено, що соціально-правові уявлення належать до найбільш складних психосоціальних явищ, які мають комплекс історичних, державно-інституційних, світоглядних, особистісних детермінант і безліч характеристик або вимірювань. Дослідження соціально-правових уявлень військовослужбовців показало певний рівень їх правового нігілізму, котрий виявляється в проблемності, нерозвиненості та несформованості їх правових поглядів, настановлень, знань, уявлень.

The topic of the article was the peculiarities of social and legal representations of servicemen. Social and legal representations of the individual are considered in the article as an understanding, evaluation of the essence of laws, legal norms, interpretation of those cases when an individual is aware of his rights and obligations, their limitations, which allows him to perceive, evaluate and present himself in various legal situations. The theoretical constructs of the article are based on the concept of S. Moskovici, who by social representations meant cognitive systems in which not just thoughts, images or attitudes about a certain object are presented, but a theory or even a field of knowledge in its special sense is reflected - as a way of identification and organization of reality. The sociality of such cognitive systems, which organize the image of the world, is determined not only (and not so much) by the fact that they represent social reality itself, but by the fact that these systems, or representations, are universally significant for many individuals, help to construct the reality of their social groups, which, in turn, determines individual behaviour. Socio-legal representations are presented in the article as a type of social representations of the individual. The authors of the model of legal development of the individual, psychologists J. Tapp and F. Levine, identified three levels of legal development of a person: law-abiding (compliance with legal norms due to fear of punishment), legal support (following laws is necessary to support the functioning of society, they can be violated for the benefit of its functioning), law-making (a combination of law and morality). The presented study of the level of development of socio-legal perceptions of servicemen, which was conducted during 2019-2021, was implemented using a shortened version of the questionnaire by J. Tapp and F. Levin. The sample consisted of two groups of servicemen. The first group is law-abiding servicemen, whose service careers have no offenses, remarks on violations of discipline or punishment for committing crimes. The second group of research subjects are military personnel, who committed offenses and were in a pre-trial detention center.

Отмечено, что социально-правовые представления относятся к наиболее сложным психосоциальным явлениям, имеющим комплекс исторических, государственно-институциональных, мировоззренческих, личностных детерминант и множество характеристик или измерений. Исследование социально-правовых представлений военнослужащих показало определенный уровень их правового нигилизма, проявляющегося в проблемности, неразвитости и несформированности их правовых взглядов, установок, знаний, представлений.
Features of social and legal concepts of military servicemen
Худавердова, А. Особливості соціально- правових уявлень військовослужбовців / Анна Худавердова // Вісник Львівського університету. Сер.: Психологічні науки. - 2022. - Вип.14. - С. 76-82. - DOI: https://doi.org/10.30970/PS.2022.14.10.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; військовослужбовці; military servants; военнослужащие; соціально-правові уявлення; socio-legal ideas; социально-правовые представления; правосвідомість; legal awareness; правосознание; когнітивні схеми; cognitive schemes; когнитивные схемы; правові норми; legal norms; правовые нормы; мораль; morality